Associations between social network properties and metabolic syndrome and the mediating effect of physical activity: findings from the Cardiovascular and Metabolic Diseases Etiology Research Center (CMERC) Cohort. Issue 1 (16th July 2020) - Kim, Kwanghyun; Jung, Sun Jae; Baek, Jong Min; Yim, Hyeon Woo; Jeong, Hyunsuk; Kim, Dae Jung; Park, Sungha; Youm, Yoosik; Kim, Hyeon Chang
Abstract : Introduction: Social isolation and loneliness are positively associated with metabolic syndrome. However, the mechanisms by which social isolation affects metabolic syndrome are not well understood. Research design and methods: This study was designed as a cross-sectional study of baseline results from the Cardiovascular and Metabolic Diseases Etiology Research Center (CMERC) Cohort. We included 10 103 participants (8097 community-based low-risk participants, 2006 hospital-based high-risk participants) from the CMERC Cohort. Participants aged 65 years or older were excluded. Multiple imputation by chained equations was applied to impute missing variables. The quantitative properties of social networks were assessed by measuring the 'size of social networks'; qualitative properties were assessed by measuring the 'social network closeness'. Metabolic syndrome was defined based on the National Cholesterol Education Program Adult Treatment Panel III criteria. Multivariate logistic regression analyses were conducted to assess association between social network properties and metabolic syndrome. The mediating effects of physical inactiveness, alcohol consumption, cigarette smoking and depressive symptoms were estimated. Age-specific effect sizes were estimated for each subgroup. Results: A smaller social network was positively associated with higher prevalences of metabolic syndrome in all subgroups, except the high-risk male subgroup. There was no clear association between social network closeness and metabolic syndrome. In community-based participants, an indirect effect through physical activity was detected in both sexes; however, in hospital-based participants, no indirect effects were detected. Cigarette smoking, alcohol consumption and depression did not mediate the association. Age-specific estimates showed that the indirect effect through physical activity had a greater impact in older participants. Conclusions: A smaller social network is positively associated with metabolic syndrome. This trend could be partially explained by physical inactivity, especially in older individuals.